Rural local knowledge for the sustainability of water resources - Rodríguez-Arévalo, Claribel; Moreno-Meneses, Jannelly (DIXI, 2023)
This study consisted of evaluating how, through environmental education and project-based learning (pbl), local rural knowledge is transformed for the sensitization and awareness of sixth grade students regarding the care and sustainability of water resources in the inspection in San Antonio (municipality of Anapoima, Cundinamarca). From a qualitative approach, with participatory action research methodology, the practices of the nineteen participating students of the San Antonio Rural Educational Institution were identified regarding the uses that have been given to the different water sources over time for the sustainability of the population. This information was obtained from direct observation instruments and techniques based on the application of a questionnaire with open questions. This research presents field work data obtained from the analysis of three categories: water resource perception, ancestral and local knowledge, and water pollution problems. In conclusion, the implementation of the pbl strategy through environmental education favored the teaching-learning process and fostered leadership and autonomy in students to learn and propose activities to raise awareness and care for water resources. At the same time, a research culture was created in the students, who were the actors in the formulation of the problem-questions and their solution, generating attitudinal changes.
Keywords: environmental education; water resources; local knowledge; sustainability; project-based learning